PENGGUNAAN MEDIA TANAM ORGANIK DAN KONSENTRASI ROOTONE F BERPENGGARUH TERHADAP PERTUMBUHAN STEK PANILI (Vanilla Planifolia Andrews) - INDRA WINTEN, KETUT TURAINI; GUNAMANTA, PANDE GEDE; GEDE PUTRA, ANAK AGUNG (Universitas Mahasaraswati Mataram, 2018)
The purpose of this study was to determine the use of the right organic planting media and how much Rootone F concentration to produce the best growth of vanilla cuttings. The study was conducted at the Tabanan University Faculty of Agriculture Experimental Garden from the beginning of August to the end of October 2017.The treatments tested included organic planting media (M) consisting of three types and Rootone F (R) concentration consisting of four levels with three replications. The results showed the interaction between the treatment of organic planting media and Rootone F concentration had no significant effect (p ≤ 0.05) on all observed parameters.The treatment of organic planting media showed no significant effect (p 5 0.05) on all parameters observed, except for the parameters of the number of roots and the length of the seedling roots, the organic cassava growing medium gave the highest yield of the number and root length of 7.17 fruits and 28.17 cm.The treatment of Rootone F concentration showed no significant effect on all parameters observed except the parameters of the number and length of seed roots, Rootone F concentration of 4 l l-1 gave the highest yield on the number and root length of seeds of 8.67 fruits and 30.11 cm.